Biofertilization for the production of cocoa seedlings (Theobroma cacao L.) CCN51 graftfor the production of organic chocolate (Agroindustria, Sociedad y Ambiente, 2024)
Current fertilization plans in cocoa crops are based on the use of inorganic fertilizers, which increase costs, risks of soil and water contamination by heavy metals, which is why other options should be considered such as: organic fertilizers, and biofertilizers, which ensure plant growth of plants, reduce costs, risks of contamination and guarantee the production of safe chocolate, which is why the objective of this research was to select the dose and type of biofertilizers or adequate commercial biostimulant in the propagation of grafted plants of cocoa (Theobroma cacao L. ) CCN51. The research was carried out in a commercial nursery, located on the La Troncal - Conchancay road, Canton La Troncal, El Cañal province, applying biofertilizers and biostimulants (Biol and worm humus) in the production of CCN51 grafted cocoa seedlings, in doses of 0, 100, 150, and 250 cc per 10 liters of irrigation water. Its effect on graft height, stem thickness and number of leaves was evaluated. The results show that the best results were obtained after applying a dose of biofertilizers of 150 cc at 30, 60 and 90 days after grafting (DDT), so it is concluded that this dose is the optimum to obtain more seedlings at nursery level, of greater vigor and that in the end will be reflected in an organic chocolate, free of contaminants and of a better price in the international market, in addition to a better price in the international market.
Keywords: chocolate, fertilization, safety, organic, sustainability